EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2024)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER2 classification. We take great pride in presenting the latest issue, which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers twenty-seven articles. The first article titled “The Adoption of the “Rain Classroom” Online Learning System among Sophomores in Chengdu, China” aims to examine the second-year students’ behavior intention and use behavior towards Rain Classroom online learning system in Chengdu, China. The second article titled “Factors Influencing the Quality of Higher Vocational Education in Chengdu during the COVID-19” explores the key factors that significantly influence the teaching quality of four different types of higher vocational colleges in the Chengdu region after the novel coronavirus epidemic. The third article titled “The Examination on Satisfaction and Behavioral Intention of Natural Science Majors Students Toward E-learning in Sichuan, China” studies the factors impacting natural science majors’ satisfaction and behavioral intention to adopt electronic learning (E-learning) at a public university in Sichuan, China. The fourth article titled “A Quantitative Study on the Factors Impacting Entrepreneurial Intention of Social Sciences Students in Chengdu, China” aims to explore the factors influencing entrepreneurial attitudes and intentions of college students majoring in Social Science at public universities in Chengdu, China. The fifth articled titled “The Assessment on Science and Engineering Undergraduates’ Satisfaction and Loyalty towards Network Teaching Platform in Chengdu, China” evaluates factors impacting science and engineering undergraduates’ satisfaction and loyalty toward network teaching platforms. The sixth article titled “Exploring Significant Factors of Chinese Workers in Shaoxing to Use Mobile Banking” determines the factors that affect how Chinese customers utilize and behave when using mobile banking, focusing on the relationship between perceived usefulness, trust, pricing value, user satisfaction, behavioral intention and use behavior. The seventh article titled “The Role of Task Technology Fit to Enhance Student Satisfaction Towards Blended Learning in Chengdu, China” examines the factors of task technology fit, confirmation, cognitive presence, teaching presence, social presence, and learner-instructors interaction to impact blended learning satisfaction of college students in Chengdu, China. The eighth article titled “Explaining Postgraduates’ Behavior on the Use of Massive Open Online Courses in Sichuan, China” aims to examine the factor impacting behavioral intention and behavior of postgraduates in their use of MOOCs in Sichuan. The ninth article titled “Affecting Factors of Gen X’s Behavioral Intention and Use Behavior of Mobile Payment in China” investigates the factors influencing the behavioral intention and use behavior of Generation X consumers in China toward mobile payments. The tenth article titled “Measuring Fourth-Year Undergraduates’ Behavioral Intention to Use Chaoxing Learning Platform in The Post-Pandemic in Anhui, China” investigates the factors that measuring undergraduates’ behavioral intention to use Chaoxing learning platform in the post-pandemic in Anhui which are determined by perceived ease of use, perceived usefulness, attitude, behavior intention, facilitating conditions, self-efficacy and subjective norm. The eleventh article titled “What Are Motivations Behind Entrepreneurship Intention and Behavior Among Postgrads in Zhejiang, China?” aims to investigate the factors that impact master’s degree students’ entrepreneurship intention and behavior in three cities: Hangzhou, Ningbo, and Wenzhou, Zhejiang Province, China. The twelfth article titled “Determinants of Behavioral Intention to Learn Arts Education of Postgraduate Students in Chengdu, China” delves into the factors that impact the behavioral intention of university students to engage in arts education. The thirteenth article titled “Influential Factors of Undergraduate Students’ Behavioral Intention toward Mobile Reading Software: A Case of a Public University in Sichuan, China” analyzes the behavioral intention of college students using mobile reading apps in Sichuan Normal University through a questionnaire survey. The fourteenth article titled “An Examination on Purchase Intention of New Energy Vehicles Among 31-60 Years Old Consumers in Sichuan, China” investigates the factors influencing consumers’ purchase intentions regarding new energy vehicles in the region of Sichuan, China. The fifteenth article titled “The Assessment on Perceived Usefulness and Satisfaction with Online Learning of Postgraduate Students in Chengdu, China” aims to assess the determinants of perceived usefulness and satisfaction among postgraduate students regarding their online learning experiences in China. The sixteenth article titled “Determining Intention of Consumers to Purchase Electric Vehicles in Chongqing, China” investigates the determinants that shape consumers’ purchase intention towards electric vehicles in the region of Chongqing. The seventeenth article titled “Empirical Investigation of Factors Influencing the Performance of Employees with Over Five Years of Work Experience in High-Tech Enterprises in China” investigates the significant factors impacting the job performance of employees in high-tech enterprises located in Chengdu, China. The eighteenth article titled “The Influencing Factors of the Music Students’ Satisfaction on Blended Learning” tests the hypotheses related to each potential influential factor in the context of music blended learning, and to assess how these factors influence the music students’ satisfaction. The nineteenth article titled “Influencers of the Postgraduate Students’ Continuance Intention to Use E-learning at a Public University in Chengdu, China” investigates how students intend to continue using e-learning at a public university in Chengdu, China. The twentieth article titled “Factors Influencing Junior College Students’ Continuance Intention with Mobile Learning at Chengdu College of Arts and Sciences, China” intends to assess the key variables significantly affecting junior college student’s continued interest in mobile learning across four majors at Chengdu College of Arts and Sciences in Sichuan, China. The twenty-first article titled “Research on Factors Affecting Behavioral Intention of Graduate Students to Use Mobile Library in Suzhou, China” investigates the significant factors affecting the behavioral intention to use mobile libraries at Soochow University, Suzhou University of Science and Technology, and Xi’an Jiaotong-Liverpool University among graduate students. The twenty-second article titled “Through the Lens of Parents: How Preschool Students Adopt U-Learning during COVID-19 in Thailand?” examines the factors influencing the acceptance and usage of the ubiquitous learning (u-learning) system among parents of preschool students in a private school in Samutprakarn, Thailand during to the COVID-19 pandemic. The twenty-third article titled “The Assessment of Significant Factors Influencing Student Satisfaction and Loyalty with Grade Classification in Yunnan, China” aims to assess the factors influencing student satisfaction and loyalty towards the grade classification at Huayu Featured School (Chaoyang Campus) in Zhaotong City, Yunnan Province, China. The twenty-fourth article titled “Investigating Parents on The Critical Factors Influencing Primary Students’ Continuance Intention to Use Tencent Class Platform in Chongqing, China” aims to explore the factors influencing parents’ continuance intention of the Tencent Class platform among students in a primary school located in Chongqing city, China. The twenty-fifth article titled “Determinants of Satisfaction and Behavioral Intention to Use E-Learning of Senior High Liberal Arts Students in Panzhihua, China” examines the satisfaction and behavioral intention of liberal arts students at a senior high school in China’s Panzhihua region to use e-learning via the Huidao Education System and the vital determining components that had a significant consequence. The twenty-sixth article titled “Examining Third-Year Students on Their Behavioral Intention and Use Behavior of DingTalk Learning Platform in Chengdu, China” aims to investigate the factors that influence students’ learning behavior in vocational colleges in Chengdu, China, using the DingTalk learning platform for mental health courses. The twenty-seventh article titled “Factors Influencing the Decision-Making of Chinese People in Choosing an Overseas Educational Consultation Firm in Beijing” reports that marketing mix factors, brand trust, and brand image affect the decision-making of Chinese people in choosing the service from an overseas educational consultation firm in Beijing.